Women Managers and The Gender-Based Gap in Access to Education: Evidence from Firm-Level Data in Developing Countries. Issue 3 (2nd July 2016) - Islam, Asif; Amin, Mohammad
ABSTRACT: A number of studies explore the differences in men's and women's labor market participation rates and wages. Some of these differences have been linked to gender disparities in education access and attainment. The present paper contributes to this literature by analyzing the relationship between the proclivity of a firm having a top woman manager and access to education among women relative to men in the country. The study combines the literature on women's careers in management, which has mostly focused on developed countries, with the development literature that has emphasized the importance of access to education. Using firm-level data for seventy-three developing countries in 2007–10, the study finds strong evidence that countries with a higher proportion of top women managers also have higher enrollment rates for women relative to men in primary, secondary, and tertiary education.